Electrically sensing Hachimoji DNA nucleotides through a hybrid graphene/h-BN nanopore. Issue 35 (28th August 2020) - de Souza, Fábio A. L.; Sivaraman, Ganesh; Fyta, Maria; Scheicher, Ralph H.; Scopel, Wanderlã L.; Amorim, Rodrigo G.
Abstract : We show that synthetic Hachimoji nucleobases can be reliably sensed by analysing the strength and duration of characteristic electrical signals generated when their presence in a nanopore modulates the conductance of an adjacent carbon wire. Abstract : The feasibility of synthesizing unnatural DNA/RNA has recently been demonstrated, giving rise to new perspectives and challenges in the emerging field of synthetic biology, DNA data storage, and even the search for extraterrestrial life in the universe. In line with this outstanding potential, solid-state nanopores have been extensively explored as promising candidates to pave the way for the next generation of label-free, fast, and low-cost DNA sequencing. In this work, we explore the sensitivity and selectivity of a graphene/ h -BN based nanopore architecture towards detection and distinction of synthetic Hachimoji nucleobases. The study is based on a combination of density functional theory and the non-equilibrium Green's function formalism. Our findings show that the artificial nucleobases are weakly binding to the device, indicating a short residence time in the nanopore during translocation. Significant changes in the electron transmission properties of the device are noted depending on which artificial nucleobase resides in the nanopore, leading to a sensitivity in distinction of up to 80%. Our results thus indicate that the proposed nanopore device setup can qualitatively discriminate synthetic nucleobases, thereby opening up the feasibility of sequencing even unnatural DNA/RNA.